Literature Review: Online Public Relations, Cara Kekinian Menjaga Citra Kementerian - Yulianto, Dhamar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
There is still little research on the application of Online Public Relations in ministries. This research describes the application of Online Public Relations in maintaining the image of various institutions. The research method uses a Literature Review from articles from 2014-2024 which were searched from 12 March-17 April 2024 using the Garuda Kemdikbud and Research Gate search engines. Of the 20 articles studied, 19 of them used the four basic elements of Online Public Relations according to Philip and Young (2009), namely Transparency, Internet Porosity, Internet as an Agent, and Richness in Content and Reach; and 4 articles link the application of Online Public Relations to Frank Jefkins' Image Theory, namely Shadow Image, Prevailing Image, Expected Image, Company Image, Compound Image, and Good and Bad Images. Furthermore, of the 20 articles studied, only 1 article discussed the application of Online Public Relations in maintaining the ministry's image. The research results reveal that the use of Online Public Relations is a contemporary way to maintain the image of the institution. This research is useful as a reference for the application of Online Public Relations in institutions, especially ministries amidst the lack of references on this matter.